Prenatal Diagnosis and Management of a Fetal Goiter Hypothyroidism due to Dyshormonogenesis. (19th December 2018) - Figueiredo, Catarina Matos; Falcão, Inês; Vilaverde, Joana; Freitas, Joana; Oliveira, Maria João; Godinho, Cristina; Dores, Jorge; Rodrigues, Maria Céu; Carvalho, Carmen; Borges, Teresa
Abstract : Fetal goiter is a rare disorder not expected to be found during a healthy woman's pregnancy. It can be a prenatal manifestation of congenital hypothyroidism due to thyroid dyshormonogenesis and it can lead to serious perinatal complications. A vascularized fetal neck mass was detected at 29 weeks' gestation of a healthy primigravida. Magnetic resonance was suggestive of goiter causing airway deviation without polyhydramnios. Maternal thyroid function was normal and thyroid antibodies were negative. Two intra-amniotic levothyroxine infusions were performed at 32 and 33 weeks. Serial imaging control showed no progression of the mass. Elective caesarean section was performed at 38 weeks. The male newborn was admitted to the intensive care unit due to cardiorespiratory insufficiency with pulmonary hypertension. Hormonal assays revealed primary congenital hypothyroidism and ultrasonography confirmed diffuse goiter. Levothyroxine was started. Currently, he is 6 years old with adequate growth and normal psychomotor development. Genetic study found a heterozygous mutation in the TPO gene.